Effect of nitrogen sources and timing on yield and nutrient uptake of hybrid rice - SUREKHA, K; REDDY, M NARAYANA; KUMAR, R M; KUMAR, C VIJAY (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted in 2 wet seasons of 1994 and 1995 in a Vertisol (Typic Pellustert) to study the differential responses of recently released rice hybrids to NH4-N and NH4 + NO3 -N sources (through urea an ca Calcium ammomum nitrate respectively) and split application of N (as 3 and 4 equal splits). Four newly released rice hybrids (,MGR 1', 'KRH 1 " 'APRH l' and 'APRH 2') using 2 checks ('Rasi' and Jaya') were tested. Between the 2 N sources tested, more stable NH4-N was found to be superior to unstable and leachable N03-N fraction in CAN in terms of both yield (6.40 and 5.44 tonnes/ha with NH4 -N in 1994 and 95 and 5.73 and 4.59 tonnes/ha with NH4 + NO3-N in 1994 and 1995 respectively) as well as nutrient uptake. N application in 4 splits, coinciding the last with flowering,improved the grain yield as well as nutrient uptake. Among the hybrids, 'MGR 1' belonging to short duration group (115-120 days) emerged as the most promising by out yielding the check 'Rasi' to the extent of 18.5 and 20% more in. 1994 and 1995respectively.